2020
DOI: 10.1016/j.heliyon.2019.e03085
|View full text |Cite
|
Sign up to set email alerts
|

Central giant cell granuloma of the mandibular condyle: A rare case and a literature review

Abstract: IntroductionCentral giant cell granuloma is a benign intraosseous lesion; tumours in the condylar region are rarely reported.Case presentationWe present the case of a 60-year-old woman with preauricular swelling, limitation of joint motion and pain on only the right side.DiscussionThe patient was evaluated based on her preoperative clinical manifestations, by orthopantomography and computed tomography (CT). CT revealed a lesion on the right condylar head. Surgery was scheduled based on this imaging finding, hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
8
0
3
Order By: Relevance
“…The World Health Organization describes CGCG as a bone lesion [ 4 , 9 , 10 ]. The treatment is controversial ( Table 1 ), and to the best of our knowledge this is the first well-documented case with the longest clinical follow-up treatment of a CGCG in the mandibular condyle described up to now.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The World Health Organization describes CGCG as a bone lesion [ 4 , 9 , 10 ]. The treatment is controversial ( Table 1 ), and to the best of our knowledge this is the first well-documented case with the longest clinical follow-up treatment of a CGCG in the mandibular condyle described up to now.…”
Section: Discussionmentioning
confidence: 99%
“…Central giant cell granuloma (CGCG) is an intraosseous lesion with three main features: the presence of fibrous connective tissue with multinucleated giant cells, hemorrhagic foci, and bone trabeculation [ 1 , 2 , 3 , 4 ]. It comprises close to 7% of all intraosseous lesions in the jaw; 60% of cases affecting patients under 30 years old, frequently in the anterior area of the mandible [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, CGCL showed higher vascular density than PG (control). Central giant cell lesions occur twice as often in the mandible than the maxilla, and commonly in the anterior compared to posterior region (Bocchialini., 2020, Khanna et al, 2018, Whitaker and Waldron, 1993. In addition, giant cell lesions are comprised of fibrocellular stroma with mononuclear cells, characterized by presence of ovoid and spindle shaped cells indicative of the activity and proliferation in the tumor (Chang et al, 2016, Chaparro-Avendao et al, 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Central giant cell granuloma (CGCG) of the jaws is not a common lesion with only 2270 cases reported in the literature in 2018 [1], the mandibular condyle is seldom affected with only 5 cases reported [2]. The CGCG is more prevalent in females (1.56 females for 1 male), and in young patients with a highest prevalence in the second and third decade of life (mean age of 25.8 years) [1].…”
Section: Introductionmentioning
confidence: 99%